2018
DOI: 10.1055/a-0650-4258
|View full text |Cite
|
Sign up to set email alerts
|

Cap-assisted colonoscopy: a meta-analysis of high-quality randomized controlled trials

Abstract: Background and study aims  Standard colonoscopy (SC) is the preferred modality for screening for colon cancer; however, it carries a significant polyp/adenoma miss rate. Cap-assisted colonoscopy (CC) has been shown to improve polyp/adenoma detection rate, decrease cecal intubation time and increase cecal intubation rate when compared to standard colonoscopy (SC). However, data on adenoma detection rate (ADR) are conflicting. The aim of this meta-analysis was to compare the performance of CC with SC for ADR amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Whereas an initial pooled analysis of 8 randomized controlled trials (RCTs) showed no significant differences, 7 high-quality RCT revealed a significant difference (OR 1.18, 95 % CI 1.03 – 1.33). However, the significance was only reached by removing 1 study 26 with a Jadad score of 1 from the initial 8 RCTs 1 ( Fig. 2a and Fig.…”
Section: What Is the Clinical Benefit Of Cc?mentioning
confidence: 98%
See 4 more Smart Citations
“…Whereas an initial pooled analysis of 8 randomized controlled trials (RCTs) showed no significant differences, 7 high-quality RCT revealed a significant difference (OR 1.18, 95 % CI 1.03 – 1.33). However, the significance was only reached by removing 1 study 26 with a Jadad score of 1 from the initial 8 RCTs 1 ( Fig. 2a and Fig.…”
Section: What Is the Clinical Benefit Of Cc?mentioning
confidence: 98%
“…In this issue of Endoscopy , Nutalapati et al 1 try to overcome this dilemma by selecting only papers of high quality for their meta-analysis. Criteria for the “high quality” was a Jadad score ≥ 3 39 .…”
Section: What Is the Clinical Benefit Of Cc?mentioning
confidence: 99%
See 3 more Smart Citations